Three novel structural variations at the major histocompatibility complex and IL12B predispose to psoriasis. (24th November 2021) - Zhen, Q.; Zhang, Y.; Yu, Y.; Yang, H.; Zhang, T.; Li, X.; Mo, X.; Li, B.; Wu, J.; Liang, Y.; Ge, H.; Xu, Q.; et al.
Summary: Background: Structural variations (SVs; defined as DNA variants ≥ 50 base pairs) have been associated with various complex human diseases. However, research to screen the whole genome for SVs predisposing to psoriasis is lacking. Objectives: To investigate the association of SVs and psoriasis. Methods: Using imputation, we performed a genome‐wide screen of SVs on five independent cohorts with 45 386 participants from the Han Chinese population. Fine‐mapping analysis, genetic interaction analysis and RNA expression analysis were conducted to explore the mechanism of SVs. Results: In total, we obtained 4535 SVs and identified two novel deletions [esv3608550, odds ratio (OR) 2·73 ( P  < 2·00 × 10 –308 ); esv3608542, OR 0·47 ( P  = 7·40 × 10 –28 )] at 6q21·33 (major histocompatibility complex), one novel Alu element insertion [esv3607339; OR 1·22 ( P  = 1·18 × 10 –35 )] at 5q33·3 ( IL12B ) and confirmed one previously reported deletion [esv3587563; OR 1·30 ( P  = 9·52 × 10 –60 )] at 1q21·2 (late cornified envelope) for psoriasis. Fine‐mapping analysis including single‐nucleotide polymorphisms (SNPs) and small insertions/deletions revealed that esv3608550 and esv3608542 were independently associated with psoriasis, and a novel independent SNP [rs9378188; OR, 1·65 ( P  = 3·46 × 10 –38 )] was identified at 6q21·33. By genetic interaction analysis and RNA expression analysis, we speculate that the association of two deletions at 6q21·33 with psoriasis might relate to their influence on the expression of HLA‐C . Conclusions: We have constructed the most comprehensive SV map for psoriasis thus far and enriched the genetic architecture and pathogenesis of psoriasis, and highlight the non‐negligible impact of SVs on complex diseases. Abstract : What is already known about this topic? Single‐nucleotide polymorphism‐based association studies have uncovered hundreds of genetic variants associated with psoriasis. However, the missing heritability and unclear underlying pathogenesis of psoriasis still exist. Several structural variations (SVs) associated with psoriasis have been reported, but they only cover a small proportion of the missing heritability and the recruited sample size was limited. What does this study add? We report the most comprehensive SV map of psoriasis so far, with a large sample size. We undertook a genome‐wide screen of SVs in five independent Han Chinese cohorts with a total of 45 386 participants. We identified two novel SVs at the major histocompatibility complex, one novel SV at IL12B and confirmed one previously reported SV at the late cornified envelope gene cluster for psoriasis. What is the translational message? A full understanding of the mechanisms contributing to psoriasis risk at established susceptibility loci should take SVs into account. The associated SVs identified will provide novel targets for diagnosis and treatment. Linked Comment:  N. Dand. Br J Dermatol 2022; 186:210–211 . Plain language summary available online